Case report: Rudimentary uterine horn with ovarian endometriosis manifested as pelvic ectopic kidney - Yin, Si-fan; Chai, Jia-gui; Feng, Run-lin; Yin, Zhi-yuan; Zhao, Shen-zhao; Zhang, Tao; Ke, Chang-xing (Frontiers in Medicine, 2023)
Background Unicornuate uterus is a congenital uterine malformation. Unicornuate uterus with rudimentary horn, ovarian endometriosis, and congenital renal agenesis are rare combinations that can be easily misdiagnosed due to the lack of typical clinical manifestations. Case summary A 19-year-old woman with pelvic pain was admitted to the hospital after a month. Physical examination was unremarkable. B-ultrasound and CT scan both indicated pelvic ectopic kidney. In addition, renal scintigraphy revealed normal perfusion and function of the right kidney, but the perfusion and function of the left kidney were not visible. A left pelvic ectopic kidney was diagnosed by preoperative images. A laparoscopic left pelvic ectopic nephrectomy was performed after adequate surgical preparation. However, the postoperative pathological diagnosis revealed a rudimentary uterine horn with ovarian endometriosis and congenital renal agenesis. Fortunately, she got recovered and was discharged from the hospital after 5 days following the operation. Moreover, she received regular follow-ups at the gynecology clinic. To date, no right adnexal or uterine abnormalities have been detected on ultrasound during the follow-up visits. Conclusion Rudimentary uterine horn with ovarian endometriosis and congenital renal agenesis are rare and are easily Misdiagnosed due to the lack of typical clinical manifestations. A gynecological examination is recommended for patients who may have this disease.